A Low-Cost, Self-Powered, Plantar Pressure Distribution Sensing Insole - Abdo-Rahmane Anas Laaraibi; Gurvan Jodin; Mario Costanza; Damien Hoareau; Samuel Margueron; Nicolas Bideau; Florence Razan (Proceedings)
Energy-autonomous wireless sensors are a promising solution for developing wearable medical, lifestyle- and performance-monitoring systems. This paper presents a low-cost, low-power and self-powered wearable intelligent pressure monitoring system based on flexible piezoresistive sensors. The encapsulated insole with an 8 × 2 sensor matrix is powered by a flexible solar panel and connected to a rigid electronic board. Data acquisition occurs via Bluetooth low-energy transmission (BLE), and the average power consumption of the insole is 113 µW.